2015
DOI: 10.1186/s12904-015-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pain flare following palliative radiotherapy for symptomatic bone metastases: multicenter prospective observational study

Abstract: BackgroundPalliative radiotherapy (RT) is an effective treatment for symptomatic bone metastases. Pain flare, a transient worsening of the bone pain after RT, has been described in previous reports with different incidence rates. The aim of the study was to prospectively evaluate the incidence of pain flare following RT for painful bone metastases and evaluate its effects on pain control and functionality of the patients.MethodsBetween June 2010 and June 2014, 204 patients were enrolled in this study and 135 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
0
28
0
2
Order By: Relevance
“…Pain flare was a frequent side effect of SBRT and was found in more than one third of patients in our series. The occurrence of pain flare is a common acute adverse effect in patients treated with CRT palliative dose schedules, with reported incidence up to 40% (Chow et al, ; Loblaw, Wu, Panzarella, & T, Smith K, Aslanidis J, Warde P, ) as confirmed by a recent multi‐institutional prospective trial (Gomez‐Iturriaga et al, ). The cumulative incidence of pain flare ranged between 23%–68% (Chiang et al, ; Pan et al, ) when patients were treated for a spinal metastases and was 10% for extraspinal sites (Owen et al, ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pain flare was a frequent side effect of SBRT and was found in more than one third of patients in our series. The occurrence of pain flare is a common acute adverse effect in patients treated with CRT palliative dose schedules, with reported incidence up to 40% (Chow et al, ; Loblaw, Wu, Panzarella, & T, Smith K, Aslanidis J, Warde P, ) as confirmed by a recent multi‐institutional prospective trial (Gomez‐Iturriaga et al, ). The cumulative incidence of pain flare ranged between 23%–68% (Chiang et al, ; Pan et al, ) when patients were treated for a spinal metastases and was 10% for extraspinal sites (Owen et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Pain flare was a frequent side effect of SBRT and was found in more than one third of patients in our series. TA B L E 2 Pain complexity according to ECS-CP (per patient and per treatment site) and correlation with steroid use, opioid medication and pain progression in patients with active pain at baseline (Gomez-Iturriaga et al, 2015). The cumulative incidence of pain flare ranged between 23%-68% (Chiang et al, 2013;Pan et al, 2014) when patients were treated for a spinal metastases and was 10% for extraspinal sites (Owen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…19 From that cohort, a total of 128 patients returned the questionnaires 4 weeks after RT and were therefore eligible for assessment of pain response and corresponding analysis of clinical factors influencing this response. 19 From that cohort, a total of 128 patients returned the questionnaires 4 weeks after RT and were therefore eligible for assessment of pain response and corresponding analysis of clinical factors influencing this response.…”
Section: Resultsmentioning
confidence: 99%
“…In patients who met all the inclusion and none of the exclusion criteria, pain associated with the bone lesion was assessed using a numeric scale from 0 to 10. This study is a secondary analysis of the population initially recruited for the 'flare study' 19 for which the main endpoint was the incidence of the flare effect in patients undergoing bone palliative radiotherapy, analysed prospectively. In patients who met all the inclusion and none of the exclusion criteria, pain associated with the bone lesion was assessed using a numeric scale from 0 to 10. This study is a secondary analysis of the population initially recruited for the 'flare study' 19 for which the main endpoint was the incidence of the flare effect in patients undergoing bone palliative radiotherapy, analysed prospectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation